A reactive oxygen species-responsive hydrogel loaded with Apelin-13 promotes the repair of spinal cord injury by regulating macrophage M1/M2 polarization and neuroinflammation - Zhiyue Li; Qun Zhao; Jiahui Zhou; Yuyan Li; Yifan Zheng; Linxi Chen (Journal of Nanobiotechnology)
Abstract Spinal cord injury (SCI) is a chronic condition whereby persistent aberrant macrophage activation hinders the repair process. During acute trauma, dominant M1 macrophages produce high levels of reactive oxygen species (ROS), leading to increased apoptosis in neurons, glial cells, and oligodendrocytes. This study investigated the specific effects of a ROS-responsive hydrogel loaded with Apelin-13 (Apelin-13@ROS-hydrogel) on macrophage polarization and neuroinflammation, thereby exploring its role in boosting SCI repair. Apelin-13@ROS-hydrogel was prepared, and its ROS-scavenging capacities were evaluated using DPPH, H2O2, and ·O2- assays. The effects of Apelin-13@ROS-hydrogel on macrophage polarization, inflammatory mediators and oxidative stress were assessed in LPS-pre-treated microglia BV2 cells and an SCI rat model. Apelin-13 was downregulated in SCI rats. Treatment with Apelin-13 improved functional recovery and reduced inflammatory factors and M1 markers but increased the M2 marker Arg-1. Apelin-13@ROS-hydrogel showed significantly higher ROS-scavenging capacities compared to the control hydrogel. Apelin-13@ROS-hydrogel decreased pro-inflammatory mediators and increased anti-inflammatory mediators in BV2 cells. Apelin-13@ROS-hydrogel enhanced the healing process and neurological functions, reducing inflammatory factors and M1 markers while increasing Arg-1 levels by day 28 in SCI rats. Collectively, Apelin-13 enhances SCI repair through macrophage regulation, M1/M2 polarization, and neuroinflammation. The ROS-responsive hydrogel further amplifies these effects, offering a promising therapeutic strategy for SCI.